DYNAMICS OF THE CONDITIONS OF FUNCTIONING OF THE SUBJECTS OF PRE- ENTREPRENEURSHIP IN THE EAEU - Kuzmina , T.; Savina , N. (EurasianUnionScientists, 2021)
The formation of a favorable business environment for the development of small and medium-sized businesses is an urgent problem for all member states of the Eurasian Union. In order to assess the efforts of the governments of the EAEU member states in creating favorable conditions for doing business, based on an in-depth analysis of changes in the position of the EAEU member states in the global Doing Business index, a factor analysis of business conditions was performed; common indicators for countries that slow down the creation of a favorable business environment in the Eurasian Union were identified, including: low level of financial support for SMEs, high interest rates on loans, excessive tax and administrative burden on business entities, as well as the lack of cooperative ties between SMEs and large businesses.